Analysis of Infiltration Well Dimensional in Kedungkandang District, Malang City, Indonesia - Azarine Nabila Jifa; Arief Rachmansyah; Aminudin Afandhi (Indonesian Journal of Environment and Sustainable Development, 2018)
Kedungkandang District is one of the fastest growing areas in Malang City and become a urban area. The implication this development is dcreasing of urban open space area by 1 - 2% per year, and followed by increased surface flow during rain. Infiltration well is one of the efficient rainwater utilization to reduce run-off. In Kedungkandang district three are different soil types which affects the permeability coefficient value for determination the dimension of infiltration well. This study aimed to determine the dimension of infiltration wells suitable for application individual infiltration wells for housing type 36, 45, 54, 70, 90 and 110.  In order to determine dimension of infiltration wells would be used, there were some analysis done: hydrology and soil permeability coefficient. The conclusion from this research was the bigger the house size, it would need a bigger dimension of infiltration well as well. From the three types of soil in Kedungkandang, the houses in alluvial fan ground type and tuff volcanic soil require a smaller size of infiltration wells than the houses located in Buring volcano mountain sediments.Key words: infiltration well, run-off